Pengaruh Volatilitas Nilai Tokar terhadap Volume Ekspor Beberapa Kelompok Komoditi Perdagangan Indonesia - Zainal, Arindra A. (Jurnal Ekonomi dan Pembangunan Indonesia, 2008)
The relationship between exchange rate volatility and export performance has been scrutinized by many economists since Bretton Wood System collapsed in 1971. Although most of the results show that there is a negative relationship between exchange rate volatility and export performance, we also find that some studies show a positive one. This study used some Indonesian group of commodities data to find the relationship between exchange rate volatility and export performance. While General Autoregressive Conditional Heteroscedasticity (GARCH) was used to calculate exchange rate volatility, this study used Pesharan & Shin ARDL cointegration test in order to find long run relationship between export performance and exchange rate volatility. Only 2 out of 7 equations tested show a long run relationship between exchange rate volatility an export performance and the signs are positive.